Ancient Greek texts and modern narrative theory: towards a critical dialogue - Grethlein, Jonas (Cambridge University Press, 2023)
"Demonstrates the limits of narratology in understanding ancient texts and forges a new approach that investigates the specific logic of ancient narrative. An invaluable introduction to ancient views of narrative but also a major contribution to a historically sensitive theory of narrative"--
Includes bibliographical references and index
Keywords: Erzähltheorie; Griechisch; Literatur